UNSUR DRAMATIK PADA FILM ALI & RATU RATU QUEENS DALAM MEMBANGUN PESAN KEKELUARGAAN - Asti Widya Adriyani; Didik Suharijadi; Soekma Yeni Astuti; Muhammad Zamroni; Denny Antyo Hartanto (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2023)
The film "Ali & the Queens" is an example of a family-themed movie. This film has an intriguing storyline as it utilizes dramatic elements to emphasize the message of family bonds. The relationship between Ali and the Queens is predominantly focused on conveying the message of kinship. Ali and the Queens are a family without any blood ties. Their relationship initially starts from a mutually beneficial arrangement. Moreover, their familiarity grows as they are fellow immigrants from the same country. The sense of family between Ali and the Queens develops while living in the same apartment, fostering closeness and care for each other. The purpose of this study is to explore how the dramatic elements in the film "Ali & the Queens" contribute to conveying the message of family. This research employs a qualitative descriptive method. Data collection techniques involve observation, documentation, and literature review. The results of the study indicate that there are ten scenes supported by dramatic elements in conveying the message of family. Three scenes are supported by conflict, three scenes by suspense, two scenes by curiosity, and two scenes by surprise.